The evaluation of the effect of the teaching model produced for automotive mechatronic on learning - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY PRESS, 2008)
In the present study, experimental results being obtained in the technical education by using the design produced by Lucas Nulle Company as related to Automotive Mechatronic have been presented. The results were analyzed with SPSS package program. The results show that the design. produced as software and hardware by Lucas Nulle Company has increased the students' success in the course and interest towards the course. According to the comparative findings between the experimental and control groups, there is a significant difference between experimental and control group's success and interest in favor of experimental group.
Keywords: automotive mechatronics; technology of education